Relationship of HbA1c, Hematocrit, Erythrocytes, MCV in Type 2 Diabetes at Husada Utama Hospital, Surabaya - Anggraeni, Devina; Suhartati, Suhartati; Yaniari, Roethmia (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2025)
Introduction: Diabetes Mellitus (DM) is a prevalent endocrine disorder characterized by hyperglycemia. Hematological parameters such as Hematocrit (Hct), Erythrocyte Count (RBC), and Mean Corpuscular Volume (MCV) have been linked to the pathological mechanisms and complications of DM. This study investigates the relationship between glycemic control status (based on HbA1c results) and these hematological parameters in type 2 DM patients. Methods: This cross-sectional study included 43 type 2 DM patients from Husada Utama Hospital, Surabaya. Data, including HbA1c, Hct, RBC, and MCV values, were collected from patient medical records. Results: The Spearman Rank test results between glycemic control status (HbA1c) and hematocrit in type 2 DM patients showed p=0.013 with r=0.374, indicating a significant moderate positive correlation (r = 0.3 to 0.5, p < 0.05). The Spearman Rank test results between glycemic control status (HbA1c) and erythrocyte count showed p=0.008 with r=0.402, also indicating a significant moderate positive correlation (r = 0.3 to 0.5, p < 0.05). However, the Spearman Rank test results between glycemic control status (HbA1c) and MCV showed p=0.052 with r=-0.302, indicating a moderate negative correlation (r = -0.3 to -0.5) that is not statistically significant (p > 0.05). Conclusion: There is a notable relationship between glycemic control and hematological parameters in type 2 DM patients. Poor glycemic control is associated with significant variations in Hct, RBC, and MCV levels, highlighting the importance of monitoring these parameters in managing diabetes complications.